miPepBase: A Database of Experimentally Verified Peptides Involved in Molecular Mimicry - Garg, Anjali; Kumari, Bandana; Kumar, Ravindra; Kumar, Manish (Frontiers in Microbiology, 2017)
Autoimmune diseases emerge due to several reasons, of which molecular mimicry i.e. similarity between the host’s and pathogen’s interacting peptides is an important reason. In the present study we have reported a database of only experimentally verified peptide sequences, which exhibit molecular mimicry. The database is named as miPepBase (Mimicry Peptide Database) and contains comprehensive information about mimicry proteins and peptides of both host (and model organism) and pathogen. It also provides information about physicochemical properties of protein and mimicry peptides, which might be helpful in predicting the nature of protein and optimization of protein expression. The miPepBase can be searched using a keyword or, by autoimmune disease(s) or by a combination of host and pathogen taxonomic group or their name. To facilitate the search of proteins and/or epitope in miPepBase, which is similar to the user’s interest, BLAST search tool is also incorporated. miPepBase is an open access database and available at http://proteininformatics.org/mkumar/mipepbase.